Effects of Local Heating and Whole-Body Hyperthermia on Neuromuscular and Cognitive Function in Young and Old Healthy Adults - Junli Wang (Baltic Journal of Sport and Health Sciences)
Background and objectives: Aging population is growing fast in European Union and worldwide (Shimizu et al., 2020). A progressive decline in neuromuscular function (Lexell et al., 1983), structural changes in the brain ( Smith et al., 2010; Zahra et al., 2019)aged 30 to 99 years, were studied with MRI. Age was related to estimated volumes of: gray matter, white matter, and CSF of the cerebrum and cerebellum; gray matter, white matter, white matter abnormality, and CSF within each cerebral lobe; and gray matter of eight subcortical structures. The results were: 1, and inefficiencies in thermoregulatory regulation (Blatteis, 2012; Yamashiro et al., 2020) were found in the old population. We conducted three experiments to investigate the eﬀects of short-term and long-term passive heating on motor performance, as well as the impact of whole-body passive heating on cognitive functioning in both healthy older and young adults.